(untitled) (Harmoni, 2012)
In Surakarta city occur the dynamics which lead to tensions and conflicts caused by the incessant propaganda by Tafsir QurΓÇÖan Assembly (MTA). This research is necessary, to understand and manipulate the social condition in order to create harmonious and tolerant situation. Focuses of the research are the historical development of MTA, propagation models, developed basic teachings and religious leaders and the governmentΓÇÖs responses to MTA. Social religious fidgetiness and tension due to the appearance of MTA indicated caused by the immature attitude and horizon of thinking of the society, especially the bottom stream of society (grassroots). They would hear the appeal of religious scholars (kyai) rather than to forward the reasoning of logical thinking. The conflict was caused by the self-defense expression, backed into a corner and then hit back with physical and rhetoric. This study used a qualitative approach.